2019
DOI: 10.1186/s12891-019-3005-2
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic posterior Atlanto-axial dislocation: case report of an atypical C1-C2 dislocation with an anterior arch fracture of C1

Abstract: BackgroundAn atypical case of a traumatic posterior C1-C2 dislocation with an anterior arch fracture of C1 is reported. A novel conservative treatment for this rare lesion is described.Case presentationAn eighty-nine-year-old male fell off a ladder at home and presented with an acute traumatic cervical spine trauma, which we believe involved a distraction mechanism. The patient was neurologically intact; he denied any weakness, numbness or paresthesia. A preoperative CT-scan demonstrated a posterior dislocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Therefore, the measurement of ADI either shows a negative value or does not accurately reflect the status of the patient's dislocation. Ghailane et al mentioned the meaning of negative ADI as an indicator that the dens of C2 migrate anteriorly and not posteriorly against the spinal cord [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the measurement of ADI either shows a negative value or does not accurately reflect the status of the patient's dislocation. Ghailane et al mentioned the meaning of negative ADI as an indicator that the dens of C2 migrate anteriorly and not posteriorly against the spinal cord [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ghailane et al [ 6 ] reported successful C1 anterior arch fracture treatment accompanying posterior AAD using closed reduction and rigid brace application. Unlike our case, in the report by Ghailane et al, congenital anomalies such as AOA were not accompanied, and the degree of posterior translation of C1 observed on CT was limited to the posterior margin of the C2 facet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior surgical approach was favored in 88% of surgically treated cases. The median postoperative follow-up time was 9 months (Interquartile range, [6][7][8][9][10][11][12]. Additional details are shown in Table 2.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Traumatic posterior atlantoaxial dislocation with fracture (TPAD) is an extremely rare entity encountered in the emergency department, with a limited number of cases reported in the literature 1–22 . The first TPAD case was reported in 1924 by Nicholson et al, 18 describing 50-year-old laborer struck by a falling tree.…”
mentioning
confidence: 99%